Life at the speed of passion : create a life of intention, purpose, and integrity - Wright, Eve (Career Press, 2014)
Life at the Speed of Passion will revolutionize the way you think about what your life looks like, what you do for a living & and why you do it. Through her meteoric rise in the corporte and sports world, Eve has learned to master the craft of confident decision-making while blending it with personal integrity to create a life more passionate and purposeful than she ever imagined.